Usher and Schumpeter on Invention, Innovation, and Technological Change - Ruttan, Vernon W. (Quarterly Journal of Economics, 1959)
Introduction, 596. — Innovation and technological change, 597. — Invention and innovation, 599. — Summary and conclusions, 605.